2020
DOI: 10.1016/j.diabres.2020.108299
|View full text |Cite
|
Sign up to set email alerts
|

Baseline characteristics and risk factors for short-term outcomes in 132 COVID-19 patients with diabetes in Wuhan China: A retrospective study

Abstract: To investigate the clinical characteristics, laboratory findings and high-resolution CT (HRCT) features and to explore the risk factors for in-hospital death and complications of coronavirus disease 2019 (COVID-19) patients with diabetes.Methods: From Dec 31, 2019, to Apr 5, 2020, a total of 132 laboratory-confirmed COVID-19 patients with diabetes from two hospitals were retrospectively included in our study. Clinical, laboratory and chest CT data were analyzed and compared between the two groups with an admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 34 publications
3
43
0
1
Order By: Relevance
“…A total of 75 articles were excluded on the basis of the full text. Finally, 16 studies [8][9][10][15][16][17][18][19][20][21][22][23][24][25][26] with 6386 COVID-19 patients were eligible and included in the meta-analysis. The process of study selection with reasons for exclusion is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…A total of 75 articles were excluded on the basis of the full text. Finally, 16 studies [8][9][10][15][16][17][18][19][20][21][22][23][24][25][26] with 6386 COVID-19 patients were eligible and included in the meta-analysis. The process of study selection with reasons for exclusion is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…The results of our study showed that symptoms of COVID-19, including fever, shortness of breath, and cough, were mostly reported in diabetic patients than in non-diabetic patients, while chest pain, sore throat, and decreased sense of smell and taste were more common in non-diabetic COVID-19 patients. In a study conducted in China, fever, dry cough, and fatigue were the most common symptoms in diabetic COVID-19 patients [ 23 ], and another study showed cough and fever as the most common symptoms in these patients [ 24 ]. A systematic review study indicated that no significant differences in signs and symptoms of these differences may be due to variation in selected sample sizes in various studies, study population, and type of collected data [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…These measurements taken at day 0 and day 4 provide an early and noninvasive indication of progression of disease to a severe course 229 . In addition, the semi‐quantitative CT pneumonia score is a valuable tool to help clinicians identify patients at higher risk of complications and mortality 113,230 . AI algorithms can identify important clinical markers correlated with COVID‐19 pneumonia lesions and also provide accurate clinical prognosis that can aid clinicians to provide risk‐stratified treatment 42 …”
Section: Laboratory Indicatorsmentioning
confidence: 99%